PENGARUH KOMPENSASI, KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. GEARINC INDONESIA - Kadek Noviantika Dewi; I Gede Rihayana; Bagus Nyoman Kusuma Putra (EMAS, 2024)
This study aims to determine the effect of compensation, job satisfaction, and work motivation on employee performance. The population in this study is all employees at PT. GEARINC INDONESIA. The sample in this study amounted to 40 respondents using saturated sampling. By using questionnaires to collect primary data, with as many as 40 respondents. The technique used is regression analysis to determine the effect of compensation, job satisfaction, and work motivation on employee performance. The results showed the results of multiple linear regression analysis, namely the t test, showed that compensation had a positive effect on employee performance with a coefficient value of 0.408 and a significance of 0.015 where this value was smaller than 0.05. Job satisfaction has a positive effect on employee performance with a coefficient value of 0.414 and a significance of 0.000 where this value is smaller than 0.05. Work motivation has a positive effect on employee performance with a coefficient value of 0.262 and a significance of 0.019 where this value is smaller than 0.05.